Acceptance of recommended vaccinations during pregnancy: a cross-sectional study in Southern Italy - Licata, Francesca; Romeo, Marika; Riillo, Concetta; Di Gennaro, Gianfranco; Bianco, Aida (Frontiers in Public Health, 2023)
Background Vaccine administration is a recommended, safe, and effective measure to protect pregnant women against vaccine-preventable diseases (VPDs). Despite available guidance, maternal immunization rates for vaccination against influenza and with the reduced antigen content tetanus-diphtheria-acellular pertussis vaccine (Tdap) in Italy remain incredibly low. The primary goal of the study was to explore what Italian pregnant women knew about VPDs and immunization during pregnancy and what factors affected their decision to be vaccinated. Methods This cross-sectional study took place between October 2021 and April 2022 in the Southern part of Italy. All consecutive pregnant women, from those attending the selected facilities on randomly selected days, were approached to request participation. The inclusion criteria for participation were age ≥18 years, the ability to understand, speak, and read Italian, and being pregnant at any gestational age. The questionnaire, using a combination of checkboxes and free text answers, consisted of 32 items divided into five parts and lasted 10 min. Results The results showed that 61% knew that the influenza vaccine is recommended and 48.7% knew that influenza could be risky during pregnancy; 74.1% wrongly reported that the Measles-Mumps-Rubella (MMR) vaccine is recommended during pregnancy. Seven out of 10 pregnant women believed that strong evidence supported the safety of vaccinations during pregnancy, and more than half (55.6%) thought they were at increased risk of severe illness with COVID-19. Women in the sample believed that vaccines received during pregnancy pose a risk of adverse events to the unborn child with a median value of 6 (IQR 3–9), on a scale ranging from 1 to 10. Similarly, the fear of contracting pertussis and influenza during pregnancy showed a median value of 6 (IQR 3–9) and 5 (IQR 3–8), respectively. Only 21.1% and 36.5% of women received influenza and Tdap vaccines during pregnancy. Conclusion Unrealistic risk perception with a negative attitude toward vaccines in pregnancy and a low percentage of vaccinated pregnant women confirm the urgency of training women to make informed choices to increase overall vaccine uptake.